Makeup as a Form of Self-Representation: Queer Beauty Vlogger: Makeup sebagai Bentuk Representasi Diri: Queer Beauty Vlogger - Devi Loveitha; Poppy Febriana (Academia Open, 2024)
This qualitative research explores makeup as a form of self-representation by queer beauty vlogger Deta Cahyaa. Applying Roland Barthes' semiotic theory, the study focuses on denotation, connotation, and myth concepts. Utilizing additional insights from Stuart Hall's Representation theory, the research employs an intensional approach to understand the nuances of makeup representation by queer beauty vlogger Deta Cahyaa in his YouTube channel. Through observational and documentary methods, the analysis reveals that queer representation in makeup has evolved beyond societal myths, transforming into a professional representation rather than reinforcing traditional stereotypes. The findings, illustrated through videos titled "Tutorial Makeup Dragon Makeup Halloween" and "Serum Foundation Pixy Makeup Going Out," contribute to reshaping perceptions surrounding makeup artists within the queer community. This study sheds light on the broader implications of makeup as a non-gender-bound profession. Highlights : Deta Cahyaa's YouTube Channel: Explore makeup representation by queer beauty vlogger Deta Cahyaa. Semiotic Analysis: Apply Roland Barthes' semiotic theory to dissect denotation, connotation, and myth in makeup representation. Evolution of Queer Representation: Examine how makeup transcends societal myths, transforming into a professional representation beyond gender stereotypes. Keywords: Makeup, Queer Representation, Semiotics, Beauty Vlogger, Gender Neutrality